Two Cases of Paraquat Poisoning from Kota, Rajasthan, INDIA. (23rd December 2012) - Khosya, Surendra; Gothwal, Sunil
Abstract : Paraquat (1, 1′-dimethyl-4, 4′-dipyridylium) is a broad spectrum liquid herbicide associated with both accidental and intentional ingestion, leading to severe and often fatal toxicity. Despite widespread availability, reports of herbicide poisoning from India are not common. Diagnosis is often difficult in the absence of proper history, nonspecific clinical features, and lack of diagnostic tests. We report two cases of fatal paraquat poisoning from a tertiary care hospital, Kota, Rajasthan, India.